Discourses and Silences: Pets in Publicly Accessible Coroners' Reports of Australian Suicides. (3rd September 2022) - Mattock, Katerina; Young, Janette; Bould, Em
ABSTRACT: Intersections of human and animal lives regarding human suicide are just beginning to be explored. Given that the investigation of human suicide poses major ethical concerns, seeking out publicly accessible information in the first instance is important. Public media reports of suicide are limited in Australia (as in many countries) by voluntary adherence to recommendations that suicides should only be reported if of substantial public significance. While macro data on suicide in Australia is available, the presence or role of animals in these human scenarios is not reported. However, some detailed coroners' investigations of suicide scenarios are available via state coroner websites. Publicly available reports between 2016 and 2020 from all Australian states and territories were manually searched for mention of pets/animals using a range of keywords in scenarios investigated as suicide. Fewer than 30 reports were identified. A critical discourse analysis was undertaken of the mentions of pets/animals in these reports. This included theming of core qualitative data. The overarching theme identified was the insignificance of pets within coroners' reports of suicide. Four subthemes were identified: pets as beloved ; potential aggressors ; incidental to reporting ; and enmeshed in human domestic violence . Despite the increasing inclusion of pets within definitions of kin, nonhuman family members are virtually invisible in Australian coronial discourses investigating possible suicides. Even when pets were noted by informants as being extremely important in the life of the deceased, there was no evidence of this relationship being seen as part of the legitimate enquiry in terms of causation or future preventative strategies. While current data are limited, given emerging research on the role of pets in human suicidality it is possible that this humancentric bias may be overlooking potentially protective and preventive approaches to suicide. It is certainly overlooking animal victims of these tragedies.